Analysis of the Root Causes of Fraud Using Risk Causal and Fraud Diamond Matrix: A Case Study on Retail Financing Company - Malinda Yusti; Triyadi Triyadi; Dona Ramadhan (Asia Pacific Fraud Journal, 2021)
Fraud risk management strategies can be carried out in three stages: prevention, detection, and response, but the most efficient stage is prevention. Fraud is part of operational risk which is defined as the risk of loss caused by the failure or inadequacy of internal processes, people, systems or technology, and external events. The perpetrators of fraud can also be analyzed using the fraud motivation model. This study aims to use the results of detection and response as input for the prevention stage using root cause analysis. This study uses the Risk Causal and Fraud Diamond (RCFD) Matrix as an analytical tool to determine the dominant root cause. This study uses 300 data samples and categorizes the root causes of fraud in the RCFD Matrix. The results show that there are three dominant root causes: 3.O System & Technology - Opportunity, 2.O Internal Process - Opportunity, and 1.P People - Pressure. These results provide recommendations for fraud prevention strategies to effectively reduce or eliminate the dominant root cause.